Antioxidants in Foods and Its Applications 2018
DOI: 10.5772/intechopen.75582
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants in Maca (Lepidium meyenii) as a Supplement in Nutrition

Abstract: Maca plant belongs to Brassicaceae such as broccoli, cabbage and radish, and has a tuberous root. With the declaration of The Food and Agriculture Organization (FAO) that maca is a forgotten and disappearing plant, the fresh, dried, powder and organic forms of it take part in nutrition as a food supplement worldwide. Studies have focused on antioxidant effects depending on its bioactive components such as phenols, glucosinolates, alkamides and polysaccharides. Antioxidant enzymes and their ability of inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 59 publications
0
6
0
1
Order By: Relevance
“…Plants have been used for therapeutic purposes since prehistoric times. In the structure of each plant, there are many important bioactive compounds such as alkaloids, flavenoids, glycosides, mucilages, saponins, tannins, and phenol, phenolic acids, coumarin, terpenes, essential oils, lectins and polypeptides [1]. These chemical compounds in plants show antiviral and antibacterial effects in other living things that consume plants and cause many effects that strengthen the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Plants have been used for therapeutic purposes since prehistoric times. In the structure of each plant, there are many important bioactive compounds such as alkaloids, flavenoids, glycosides, mucilages, saponins, tannins, and phenol, phenolic acids, coumarin, terpenes, essential oils, lectins and polypeptides [1]. These chemical compounds in plants show antiviral and antibacterial effects in other living things that consume plants and cause many effects that strengthen the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…It contains dietary fiber in a range of 15.6 to 26% [7]. Further, a wide variety of potential functional molecules included glucosinolates, functional polysaccharides, alkamides [3,8], and antioxidant and anti-inflammatory compounds have been reported [9].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, estradiol replacement reduces oxidative stress in OVX rats 35 . On the other hand, chemical composition of L meyeni shows polyphenols, glucosinolates, alkamides, and non‐starch polysaccharides which have potent antioxidant activity in vitro 36 can also increase the cellular antioxidant status of superoxide dismutase, glutathione peroxidase, and glutathione s‐transferase levels in hereditary hypertriglyceridemic rats, 37 or even in alcoholic mice 38 . It has been reported that antioxidant capacity of alkaloids are more relevant than polyphenols metabolites in L. Meyenii , 39 and black maca presents a higher antioxidant activity than red maca 40 .…”
Section: Discussionmentioning
confidence: 99%